The world this week. (Economist, 2017)
The article presents world news briefs of the week of January 7, 2016. It states that U.S. President Barack Obama had 35 Russian diplomats expelled from the U.S. and imposed economic sanctions in response to interference by Russian hackers in the 2016 Presidential election. It mentions the attack by an Islamic State gunman at a nightclub in Istanbul, Turkey during New Year's Day festivities which killed at least 39 people. It reports on strained relations between the U.S. and Israel.